PENGEMBANGAN DOMINO PECAHAN BERBASIS OPEN ENDED UNTUK MENINGKATKAN KEMAMPUAN BERPIKIR KREATIF SISWA SD - Mohammad Faizal Amir; Mahardika Darmawan Kusuma Wardana (UNIVERSITAS MUHAMMADIYAH METRO, 2017)
This research aims to develop an open ended domica-based cards in improving creative thinking ability of elementary school students on the material fractions and find out the results of its development. The development was done by using Plomp model which consists of: (1) the initial Investigation, (2) design, (3) the realization/construction, (4) the testing, evaluation, and revision, (5) implementation. The research subjects at the the testing, evaluation, and revision phase is 38 6th grade students of SDN Kenongo 1 Tulangan Sidoarjo. While in the implementation phase, the ubject is 40 6th grade students SDN Kalitengah 1 Tanggulangin Sidoarjo. Data collection techniques use creative thinking tests, observation of students' creative thinking activities, questionnaires, and documentations. The results concluded that the open ended domica-based card to enhance the creativity of elementary school students produced two sets of cards in the material of common fraction and mixed fractions, as well as a set of cards consisting of whole fractions sub material (regular, percent, and decimal fractions), each of which contains 66 cards. Domica-based card open ended trial results good quality because it has met the criteria of validity, practicality, and effectiveness to train the creativity of students in the aspect of flexibility, elaboration, and novelty.